Adherence to European ovarian cancer guidelines and impact on survival: a French multicenter study (FRANCOGYN). Issue 11 (4th October 2021) - Jochum, Floriane; De Rozario, Tamara; Lecointre, Lise; Faller, Emilie; Boisrame, Thomas; Dabi, Yohann; Lavoué, Vincent; Coutant, Charles; Touboul, Cyril; Bolze, Pierre-Adrien; Bricou, Alexandre; Canlorbe, Geoffroy; et al.
Abstract : Objective: The primary objective of the study was to validate the European Society for Medical Oncology (ESMO)–European Society of Gynecologic Oncology (ESGO) ovarian cancer guideline as a method of assessing quality of care, and to identify patient characteristics predictive of non-adherence to European guideline care. The secondary objectives were to analyze the evolution of practices over the years and to evaluate heterogeneity between centers. Methods: This retrospective multicenter cohort study of invasive epithelial ovarian cancer reported to the FRANCOGYN database included data from 12 French centers between January 2000 and February 2017. The main outcome was adherence to ESMO–ESGO guidelines, defined by recommended surgical procedures according to the International Federation of Gynecology and Obstetrics (FIGO) stage and appropriate chemotherapy. Mixed multivariable logistic regression analysis with a random center effect was performed to estimate the probability of adherence to the guidelines. Survival analysis was carried out using the Kaplan–Meier method and a mixed Cox proportional hazards model. Results: 1463 patients were included in the study. Overall, 317 (30%) patients received complete guideline adherent care. Patients received appropriate surgical treatment in 69% of cases, while adequate chemotherapy was administered to 44% of patients. Both patient demographics and disease characteristics were significantly associated with the likelihood of receiving guideline adherent care, such as age, performance status, FIGO stage, and initial burden of disease. In univariate and multivariate survival analysis, adherence to the guidelines was a statistically significant and independent predictor of decreased overall survival. Patients receiving suboptimal care experienced an increased risk of death of more than 100% compared with those treated according to the guidelines (hazard ratio 2.14, 95% confidence interval 1.32 to 3.47,  p<0.01). In both models, a significant random center effect was observed, confirming the heterogeneity between centers (p<0.001). Conclusions: Adherence to ESMO–ESGO guidelines in ovarian cancer was associated with a higher overall survival and may be a useful method of assessing quality of care.